Fabrication of micro-mixer on printed circuit board using electrochemical micromachining. Issue 2 (November 2019) - Singh, Jitendra; Bhattacharya, Shantanu
Abstract: Electrochemical micromachining (ECMM) has been mostly carried out in situations demanding precision, complexity in the shapes of final components and in case the surface integrity and performance are independent of the machining process. In this work, the following have been demonstrated: The first part of the work demonstrates the experimental setup for ECMM that is used to fabricate a micro-mixer on a printed circuit board (PCB) substrate by using a single point electrochemical machining tool with a tip diameter—150 µm. The method is able to show a promising route of fabrication where the circuit lines on a PCB substrate can be printed with high yield and processing speeds. The second part of the article points out that machining can be carried out on PCB substrates through electrochemical processes using a single point tool and a minimum feature size of 243 µm can be machined with a fine tolerance of 0.025 µm and roughness = 3.0459 µm 7.2404 µm. The third part of the article reports the geometrical parameters of a relatively complex geometry of a micro-mixer which is arrived at through a COMSOL based simulation platform that is fabricated using the mentioned manufacturing process. The process is further validated through the design of experiments, and fluid flow and mixing behaviour on the fabricated structure is evaluated through an epifluorescence microscope. The advantages that this technique may offer is in terms of achieving an overall low feature size in comparison to micro-milling and avoiding the complexities of lithography-driven processes to produce a process which has a much lower equipment dependency, is environmentally benign in comparison to the lithography driven techniques and is overall low in cost.